Biomedical Informatics Discovering Knowledge in Big Data - Holzinger, Andreas (Springer International Publishing : Imprint: Springer, 2014)
This book provides a broad overview of the topic Bioinformatics (medical informatics + biological information) with a focus on data, information and knowledge. From data acquisition and storage to visualization, privacy, regulatory, and other practical and theoretical topics, the author touches on several fundamental aspects of the innovative interface between the medical and computational domains that form biomedical informatics. Each chapter starts by providing a useful inventory of definitions and commonly used acronyms for each topic, and throughout the text, the reader finds several real-world examples, methodologies, and ideas that complement the technical and theoretical background. Also at the beginning of each chapter a new section called "key problems", has been added, where the author discusses possible traps and unsolvable or major problems. This new edition includes new sections at the end of each chapter, called "future outlook and research avenues," providing pointers to future challenges.